Monopolization, classification and symbolic violence: Pierre Bourdieu's contribution to the analysis of State Nationalism. Issue 2 (4th May 2021) - Rius-Ulldemolins, Joaquim
ABSTRACT: The study of nationalism is usually split into its macro-sociological dimension and the political and coercive aspects on the one hand, and into micro-sociological, psychological and symbolic aspects on the other. Pierre Bourdieu's methodological structuralist approach and his concepts of habitus and doxa give us a better understanding of nationalism in its dominant form – State Nationalism. These concepts shed light on: (a) the framework and micro-dimension of The State's monopolization of symbols; (b) the battle lines between 'centre' and 'periphery'; (c) hierarchicalisation; (d) the invisible way in which nationalism as the dominant ideology creates coherent cognitive systems that dovetail with the institutional structure. Thus one of State Nationalism's greatest victories is to pass itself off as Universalist and disinterested. In so doing, it fosters symbolic violence and adherence to this doxa .